2011
DOI: 10.1603/ec10188
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Insecticide Resistance in Introduced Horn Fly (Diptera: Muscidae) Populations and Implications for Management

Abstract: The horn fly, Haematobia irritans (L.) (Diptera: Muscidae), was introduced to Chile in the beginning of the 1990s. Since its introduction, farmers have controlled this pest almost exclusively with insecticides. To understand the consequences of different control strategies on the development of insecticide resistance and their persistence, a field survey was conducted at eight farms in the south of Chile to characterize insecticide resistance in field populations and resistance mechanisms. Horn fly samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
(78 reference statements)
1
9
2
Order By: Relevance
“…The status of pyrethroid resistance in Brazil is similar to what has been observed in other South American countries, such as Uruguay (MARQUES et al, 1997), Argentina (GUGLIELMONE et al, 2001) and Chile (OYARZÚN et al, 2011), where widespread horn fly resistance to pyrethroids has been detected regionally or nationally.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The status of pyrethroid resistance in Brazil is similar to what has been observed in other South American countries, such as Uruguay (MARQUES et al, 1997), Argentina (GUGLIELMONE et al, 2001) and Chile (OYARZÚN et al, 2011), where widespread horn fly resistance to pyrethroids has been detected regionally or nationally.…”
Section: Resultssupporting
confidence: 78%
“…Previous studies in South American countries also failed to detect resistance to diazinon (MARQUES et al, 1997;GUGLIELMONE et al, 2000;BARROS et al, 2002;OYARZÚN et al, 2011), thus suggesting that if it is occurring, it either must be still at a low frequency or must be confined to particular sites. So far, horn fly resistance to OPs has been reported only in the USA (CILEK et al, 1991;STEELMAN et al, 1994;BARROS et al, 2001) and Mexico (GARCÍA et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Actually, the evidences gathered by previous studies (GUERRERO ;BARROS, 2006;BARROS et al, 2007;SABATINI et al, 2009) have already suggested that the major mechanism behind pyrethroid resistance in the country would be metabolic, most likely oxidative. This situation contrasted with findings abroad, where higher frequencies of kdr have been reported and this mechanism seemed to play a more important role (JAMROZ et al, 1998;LI et al, 2003;OYARZÚN et al, 2011).…”
Section: Resultscontrasting
confidence: 99%
“…High levels of insecticide resistance are also observed for Aedes aegypti in three Brazilian states (Rio de Janeiro, Espírito Santo and Ceará) [ 84 , 85 ] and for the house fly Musca domestica in three Argentinean populations [ 86 ]. The horn fly, Haematobia irritans , showed high frequencies of the kdr mutation, associated with high levels of pyrethroid resistance, in southern Chile [ 87 ]. Our results, in addition to many other studies, indicate that insecticide resistance is widespread throughout South America.…”
Section: Discussionmentioning
confidence: 99%